- #1

- 91

- 0

## Homework Statement

The binomial expansion of [itex](1+x)^n[/itex], n is a positive integer, may be written in the form

[itex](1+x)^{n} = 1+c_{1}x+c_{2}x^{2}+c_{3}x^{3}+...c_{r}x^{r}+...

[/itex]

Show that , if [itex]c_{s-1}[/itex], [itex]c_{s}[/itex] and [itex]c_{s+1} [/itex] are in arithmetic progression then [itex](n-2s)^{2} =n+2[/itex]

## Homework Equations

## The Attempt at a Solution

"[itex]c_{s-1}[/itex], [itex]c_{s}[/itex] and [itex]c_{s+1} [/itex] are in arithmetic progression" infers that

[itex]\frac{c_{s-1} +c_{s+1}}{2}=c_{s}\\

\frac{\binom{n}{s-1} + \binom{n}{s+1}}{2}=\binom{n}{s} \\

\frac{n!}{2(n-s+1)!(s-1)!} + \frac{n!}{2(n-s-1)!(s+1)!} = \frac{n!}{(n-s)!s!}\\

\frac{(n-s)!s!}{(n-s+1)!(s-1)!} + \frac{(n-s)!s!}{(n-s-1)!(s+1)!} = 2\\

\frac{s}{n-s+1} + \frac{n-s}{s+1}= 2\\

\frac{n-s}{s+1} = 2- \frac{s}{n-s+1}\\

n+2= (s+1)(2- \frac{s}{n-s+1})+s+2\\

n+2= 2(s+1)- \frac{s(s+1)}{n-s+1}+s+2

[/itex]

At this point it's getting messy, so I set s to 1 and n to 2 and get n+2 = 6 as opposed to the 0 I get when I do the same susubstitution for [itex](n-2s)^{2}[/itex]

Can someone please point out what I have done wrong.